Enantio‐ and Diastereoselective Cyclopropanation of 1‐Alkenylboronates: Synthesis of 1‐Boryl‐2, 3‐Disubstituted Cyclopropanes. (2nd January 2018) - Carreras, Javier; Caballero, Ana; Pérez, Pedro J.
Abstract: A novel, highly enantio‐ and diastereoselective synthesis of 1‐boryl‐2, 3‐disubstituted cyclopropanes has been developed by means of the cyclopropanation of alkenylboronates with ethyl diazoacetate in the presence of catalytic amounts of a chiral copper(I) complex. The products can also be directly accessed from alkynes through an operationally simple, sequential hydroboration–cyclopropanation protocol. The resulting enantioenriched 1‐boryl‐2, 3‐disubstituted cyclopropanes are versatile synthetic intermediates that undergo further transformations at the carbon–boron bond.